The Association Between Asymptomatic Placental Malaria Infection and Pregnancy Outcome in Delta State, Nigeria - Obi , Sadiatu Sally; Sumner , Davies W; Garrett-Cherry , Tiana Garrett-Cherry; Adebe , Gabriel Aondofa; Adjekuko, Collins Ohwonigho; Nze , Francis Ikechukwu; Odili-Igba, Ann Odili-Igba; Ogirisen , Felix Ogirisen (International Journal of Health Sciences, 2023)
Purpose: Parturients in the Sub-Saharan African are susceptible to malaria disease due to their reduced immunity during pregnancy. Asymptomatic placental malaria causes neonatal and maternal mortalities, preterm deliveries as well as low birth weight babies. Current studies on malaria in pregnancy indicated that the risk factors are location specific, and there are limited studies in Nigeria on asymptomatic placental malaria and pregnancy outcome (babies birth weight and delivery term). The purpose of this study was to determine the association between asymptomatic placental malaria infection and pregnancy outcome (baby's birth weight and delivery term) among parturients in Asaba, Delta State, Nigeria. Methodology: Quantitative methodology with primary and secondary healthcare facility data from 483 subjects aged 18-49 years generated from four healthcare facilities between May and July 2021 was used for this study. The Socio-Ecological Model framework was used to describe how parturients can achieve enhanced pregnancy outcome through the utilization of multi-levels of supports to enhance the compliance of pregnant women to the existing malaria interventions. The research questions and hypotheses were tested with the binomial logistic regression. Result: The findings showed a statistically significant association between baby's birth weight, delivery term and placental malaria parasitemia (PMP), in the study population. Also, the identified risk factor for baby's birth weight in this study was gravidae, while that of delivery term was age groups, gravidae, ITN frequent use and ANC attendance. Unique Contribution to Theory, Policy and Practice: The findings of this study could inform malaria control policymaking in Asaba and Delta State on tracking and treating asymptomatic malaria among underserved pregnant women accessing antenatal services to improve baby's birth weight, delivery term, and the associated complications.